THE RESULTS OF OWN-STAGE SURGICAL TREATMENT OF PATIENTS WITH ACUTE PILONIDAL SINUS DISEASE - Tsema, Ye.V.; Sidorenko, I.I.; Dibrova, Yu.V. (World of Medicine and Biology, 2013)
The results of radical surgical treatment of 174 patients with acute pilonidal abscess who were treated by urgent radical operation are presented in the article. 26 (14.9%) patients were conducted with wide excision and marsupialization of wound. 31 (17.8%) patients were treated by wide excision and wound closure by vertical U-type multi-stitch sutures. 29 (16.7%) patients were conducted with wide excision and wound closure by U-type horizontal («turnstile») sutures. 34 (19.5%) patients were treated by Bascom’s I operation. 54 (31.0%) patients were treated by proposed ultrasound curettage of pilonidal sinus. The results of treatment patients follow from 1 to 3 years. The patients with acute pilonidal abscess after operation have such complications: 56 (32.2%) patients have wound abscess, 19 (10.9%) patients have primary wound dehiscence, 24 (13.8%) patients have secondary wound dehiscence, 14 (8.0%) patients have wound hematoma, 19 (10.9%) patients have recurrent of disease. Patients who were treated by Bascom's I operation and ultrasound curettage pilonidal sinus have authentically less (P = 0.02) cases recurrent of disease and noninflammatory complications. The using of low-traumatic surgical methods (Bascom's I operation, ultrasound curettage pilonidal sinus) permit to authentically decrease (P = 0.02) frequency of postoperative complications and recurrent of pilonidal disease.
Keywords: acute pilonidal abscess; pilonidal sinus disease; radical surgical treatment; Bascom's I operation; ultrasound curettage